The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.28992/ijsam.v4i2.225
|View full text |Cite
|
Sign up to set email alerts
|

CEO Compensation and Firm Performance: The Role of ESG Transparency

Abstract: Chief executive officers (CEOs) of environmental, social, and governance (ESG) firms are known to take lesser pay and engage themselves in corporate social responsibility activities to achieve the dual objective of the enhancement of firm’s performance as well as benefit for stakeholders in the long run. This study examines the role of ESG transparency in strengthening the impact of firm performance on total CEO pay in ESG firms. A panel of 67 firms for the period of 2014–2019 has been analyzed using the two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 69 publications
1
20
1
10
Order By: Relevance
“…So, the role duality of CEO has no significant effect on CSD for the corporations listed on the sustainability index. This result is conflicting with Shamil et al (2014); Rath et al (2020) who suggest a significant positive effect for CEODU on CSD. Regarding the control variables, the findings that LOGASS, ROA, and DEBT do not affect CSD for the corporations listed on the sustainability index.…”
Section: Variablesmentioning
confidence: 65%
“…So, the role duality of CEO has no significant effect on CSD for the corporations listed on the sustainability index. This result is conflicting with Shamil et al (2014); Rath et al (2020) who suggest a significant positive effect for CEODU on CSD. Regarding the control variables, the findings that LOGASS, ROA, and DEBT do not affect CSD for the corporations listed on the sustainability index.…”
Section: Variablesmentioning
confidence: 65%
“…Similarly, Suttipun (2021) reported a positive correlation between CEO compensation and ESG disclosure. Conversely, Rath et al (2020) discovered that a transparent process of ESG disclosure is associated with a reduction in CEO compensation. Additionally, Al‐Shaer and Zaman (2019) found that the presence of external assurance on environmental reporting positively impacts the inclusion of sustainability clauses in compensation contracts.…”
Section: Slr Resultsmentioning
confidence: 99%
“…In terms of CEO compensation, the studies examined both monetary benefits (Rath et al, 2020) and non-monetary benefits (Deng & Gao, 2013). The environmental performance aspect was investigated using concepts such as sustainability performance (Ahn, 2020), environmental strategies (Fan et al, 2021), environmental innovation (Quan et al, 2021) and environmental responsibility (Zhang, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, with the right stimulus, organizational decision-makers can focus on activities that enhance sustainable value creation and, thus, long-term value. The literature has documented the positive link between ESG performance and financial performance (Rath et al , 2020). Increased consumer willingness to bear economic development costs (McWilliams and Siegel, 2001), reputation enhancement (Brammer and Millington, 2005) and contract cost reduction (Jones, 1995) are mechanisms that improve the banks’ performance and that stem from their commitment to achieving SDGs.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%